The humanization of care in intensive care units (Research, Society and Development, 2024)
Objective: To reflect on the benefits of humanizing nursing care in the ICU. Method: Integrative literature review, bibliographic study, carried out from August 2023 to February 2024 in the databases of the Virtual Health Library and the SCIELO Library, after filtering with full text, in the last 8 years, 2017 a 2024, and in English and Portuguese and, after the systematic analysis of two articles, 15 scientific products were selected that corroborated the objective of the study. Results: The data analytical process brought important results, such as the significance of understanding the importance of the confluence of the intimate professional-patient relationship which, when properly implemented, confirms the guidelines standardized by the National Humanization Policy: physical contact; Health education; empathetic, welcoming and hierarchical communication; acceptance of desires and fears not only of patients, but also of their families; enabling family integration of patients; individualized assistance to the specific needs of patients; promoting the maximum possible comfort; in addition to, above all, individual humanization of the professional. Conclusions: Therefore, we can say that humanization is an important tool in daily nursing practice, enabling reception, communication, acceptance of treatment, patient safety, contributing to efficient and quality care in Intensive Care Unit environments.